Perbedaan Hasil Pemeriksaan Hematologi yang Segera Dilakukan Pemeriksaan dan yang Ditunda pada Suhu Ruangan dan Refrigerator menggunakan Sysmex XP-300: The Difference Between the Hematology Examination that was Immediately Carried Out and which was Delayed at Room Temperature and Recommended using a Sysmex XP-300 - Nathalya Dwi Kartika Sari; Gilang Nugraha; Brina Thursina Dibiasi; Mirshall Abiedama Prayoga (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
An automatic hematology analyzer (hematology analyzer, ha) is a routine hematology examination tool used extensively in clinical laboratory services. Sysmex XP-300 is the HA 3-part diff that is the most straightforward ha impedance examination of the number of cells based solely on cell sizes. The storage temperature and incubation times affected the complete blood count examination. This study determined the difference between hematology and EDTA's immediate examination of blood samples and was delayed at room temperature and temperature using a Sysmex XP-300. Hopefully, this research could be developed with a method of validation of checks to minimize errors in clinical laboratories. Experimental research methods with a pre-experimental design through the one group afflicted posttest design with a sample of as many as 15 laboratories, and we analyzed with ANOVA. The results of this study have WBC, RBC, HGB, HCT, MCV, MCH, and MCHC different results at room temperatures 2, 24, 48, and 72 hours compared to temperature fluctuations; the PLT parameters alone show no significant difference when it comes to prompt examinations with delays in the application. Morphology of erythrocyte is influenced by temperature, and storage should be hypotensive.